DISPLAY AND QUANTITATIVE ASSESSMENT OF DISTRIBUTIONS OF EARTHQUAKE FOCAL MECHANISMS - Frohlich C. (My University, 2001)
This paper describes quantitative methods for evaluating the distribution of focal mechanism orientations of groups of earthquakes, and shows how to display this distribution on a triangle diagram. We present a χ2-based statistical test for determining whether two sets of focal mechanisms are drawn from distinct populations. We apply these methods to 3625 better-determined mechanisms for shallow earthquakes in the Harvard Centroid Moment Tensor (CMT) catalogue; we describe the distributions of mechanisms in the whole catalogue and for catalogue subsets in some specific tectonic environments. In addition, we explore the geographical locations of mechanisms with orientations that occur relatively infrequently, that is, mechanisms that are unlike thrust, normal, or strike-slip mechanisms. Such mechanisms are relatively rare along mid-ocean ridges and in oceanic subduction zones. The majority of these unusual mechanisms occur along plate boundaries where crustal thickness is highly variable, and in regions where the plate convergence direction becomes oblique and thus relative motion changes from convergence to transform motion.